Analysis of Students' Mathematics Learning Independence Based on Gender and Aspects in High School - Zafrullah, Zafrullah; Sultan, Jumriani; Ayuni, Rizki Tika; Uleng, Andi Tenri (Perspektif Pendidikan dan Keguruan, 2024)
Independent learning in mathematics plays a very vital role in the educational process, because through this independent learning, students have greater opportunities to develop their potential independently in understanding mathematical concepts, expanding understanding, and exploring complex concepts, which in turn in turn will help them become more productive and effective mathematics learners in their efforts to achieve their academic and personal goals. This research aims to analyze learning independence based on gender, aspects and overall. This research is quantitative in nature with research subjects of 277 high school students in Natuna, Riau Islands, Indonesia. The instrument used is the learning independence instrument which has been validated with 25 statement items. The data analysis technique uses quantitative descriptive analysis. The research results show that the female gender shows a higher average percentage, reaching 76.03% with "Good" status. This indicates that in the independent aspect of learning mathematics, women tend to show better performance compared to men. Meanwhile, the final results show that the final total score for independent learning for all respondents reached 71,889%, indicating relatively good performance in facing the challenges of independent learning.